Synthesis, antioxidant and photoprotection activities of hybrid derivatives useful to prevent skin cancer - Reis, Juliana Santana [UNESP]; Correa, Marcos Antonio [UNESP]; Chin, Chung Man [UNESP]; Santos, Jean Leandro dos [UNESP] (Elsevier B.V., 2014)
Chronic ultraviolet (UV) radiation exposure is a major cause of skin cancer. A novel series of hybrid derivatives (I-VIII) for use in sunscreen formulations were synthesized by molecular hybridization of t-resveratrol, avobenzone, and octyl methoxycinnamate, and were characterized. The antioxidant activity values for VIII were comparable than to those of t-resveratrol. Compounds I-III and VI demonstrated Sun Protector Factor superior to that of t-resveratrol. Compounds I and IV-VIII were identified as new, broad-spectrum UVA filters while II-III were UVB filters. In conclusion, novel hybrid derivatives with antioxidant effects have emerged as novel photoprotective agents for the prevention of skin cancer. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Sunscreens; Photoprotection; Antioxidant; UV radiation; UV filters; t-Resveratrol; Avobenzone; Octyl methoxycinnamate; Molecular hybridization